Does former learners' of the Star for Life Programme comply with the model beyond the learning workshops? : an evaluation of the long-term impact of the programme objectives on former learners' at Siphosabadletshe High School in the province of KwaZulu-Natal in South Africa - Asplund, Peter Brengt Paul (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.